Ritual Keislaman melalui Ratibul Haddad sebagai Sarana Pencegahan Kenakalan Remaja - Lailatul Maghfiroh (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
This paper reveals about the implementation of Islamic rituals through ratib al-Haddad as a means of preventing juvenile delinquency, and analyzes the influence of Islamic rituals through ratib al-Haddad as a means of preventing juvenile delinquency. This research method uses a type of qualitative research with a case study design. Data collection techniques using observation techniques, interviews, and documentation. The data analysis technique uses the Miles and Huberman models with the stages of data reduction, data presentation, and drawing conclusions. This research was conducted at Ngingas Waru Sidoarjo, this activity was carried out every Saturday and Sunday evening which began with reading qoshidah mudhoriyah, then continued with the reading of ratib al-Haddad which began with tawassul, then read shalawat rejecting the annual disaster, then continued with tahlil and ended with prayer, This activity was attended by teenagers from the surrounding area, by participating in this activity the youth made Saturday night time to plant goodness..